Solar-wind street lighting - 1 - Yeo, Howe Li. (2012)
In this report, a maximum power point tracker was designed, constructed and tested for the PV portion of a solar-wind street lamp. Experiments were conducted on the roof of S2 to obtain the electrical characteristics of the solar panel for simulation and design. An ATMEGA8 microcontroller along with a DC-DC converter, a current sensing circuit and a voltage sensing circuit was used to implement the Perturb and observe algorithm (P&O). In addition to this, the design of a master controller consisting of a single inductor multi input multi output(SI MIMO) DC-DC converter that manages the power flow of the input energy sources was also explored. The SI MIMO portion was simulated using PSPICE but results were inconclusive. Programming aspects involved in the master controller’s logic, in particular the use of the inter-integrated circuit (I2C) protocol was also discussed.